Distribution patterns of suitable habitat for Cycas tanqingii in the China-Laos-Vietnam region under the interaction of climate change and pest factors - Jia Li; Churui Li; Cairong Yue; Wen Wang; Hongbin Luo; Lanzhong Zhang; Ting Chen; Jian Shen; Zihan Teng (Ecological Indicators, 2025)
The cycad Cycas tanqingii is an endangered species susceptible to climate change and pest infestations. Global warming is expected to shorten the development cycles of insect pests, prolong periods of damage, increase population sizes and generational frequency, and facilitate migration to higher altitudes and latitudes. These changes could worsen the threat to Cycas tanqingii. Consequently, predicting potential suitable habitat can provide a proactive theoretical foundation for conservation efforts. This study used MaxEnt to simulate and predict the current and possible future distribution, changes in habitat area, shifts in the centroid of suitable habitat, changes in conservation status, and ecological niche dynamics of Cycas tanqingii. The analysis was based on 199 distribution sites of Cycas tanqingii obtained from field surveys, the GBIF and various local bibliographies, and took into account the four environmental variables: climate, soil, topography, and pests. Simulations considered pest and abiotic factors across three greenhouse gas concentration scenarios (SSP126, SSP370, and SSP585). The results indicated that under the assumed changes in pest and abiotic factors, the most significant environmental factor influencing the distribution of Cycas tanqingii changed from Precipitation of Warmest Quarter to the pest factor. Furthermore, the current area of suitable habitat for Cycas tanqingii would be reduced from 19.2784 × 104 km2 to 8.6177 × 104 km2. Moreover, when pest factors are included, the conservation status of Cycas tanqingii changes from “vulnerable” to “endangered”, and the centroid of suitable habitat shifts northwest within the study area. At the same time, the ecological niche of Cycas tanqingii stabilizes. The findings of this study have substantial practical implications, offering a theoretical framework for developing effective conservation strategies for Cycas tanqingii.